Two views of assistance. (December 2017) - Maffettone, Pietro; Muldoon, Ryan
The article makes two substantive contributions to the existing literature on the ethics of international assistance and global justice. First, it builds what we take to be a widely held set of propositions about international assistance into a consistent view (i.e. the relief view), and articulates a strong case against its desirability. Second, it sketches a more attractive alternative (i.e. the development view). To do so the article uses Sen's idea of agent-oriented development as a starting point while at the same time providing a generalization of Sen's account and a justificatory framework that does not rely on the capability approach.